Sistem Informasi Geografis Stasiun Pemantauan Spektrum Frekuensi Radio Di Wilayah Bali - I Nyoman Suada; I Made Oka Widyantara (Ikatan Ahli Informatika Indonesia, 2025)
The Radio Frequency Spectrum Monitoring Center Denpasar must carry out observation and monitoring. In carrying out this monitoring, there are eight fixed and transportable monitoring stations that have been placed in several locations in the Bali Province to carry out monitoring. However, given the scattered distribution of Radio Station Licenses across various locations in cities/regencies in the province of Bali, there are blind spots where some Radio Station Licenses are not covered by fixed and transportable stations. This will affect the achievement of the observation and monitoring performance agreement targets of the Radio Frequency Spectrum Monitoring Center. In practice, observations and monitoring must be carried out in uncovered locations using mobile or portable monitoring devices. The selection of monitoring locations is based on the distribution of ISRs, the coverage radius of monitoring points, and the conditions and contours of the area. This ensures that these locations are effective and efficient in providing optimal results, especially in achieving the observation and monitoring performance agreement targets. The analysis method utilizes the QGIS application, where optimal locations are identified based on the visual representation of locations in Google Earth, the locations of fixed and transportable stations, and the distribution of Radio Station Licenses, which are then visualized in the QGIS application. Based on the results of the analysis and visualization, it was found that the percentage of performance agreement achievement or the number of radio station licenses monitored at the monitoring location was achieved. The nine cities/regencies in Bali Province have the following achievement percentages: Badung 99%, Tabanan 85%, Klungkung 100%, Gianyar 99%, Karangasem 85%, Denpasar 100%, Bangli 100%, Jembrana 86%, and Buleleng 89%.